Experiments, modelling and analysis of fretting fatigue for inconel 718 and TI-6AL-4V under time-varying contact normal load at room and high temperature - Almeida, Gabriel Magalhães Juvenal (2022)
Tese (doutorado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Mecânica, 2022.